Incompetence in refugee protection under the provisions of the international law - Almuhaisan, Heba Jawdat (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aims to help the refugees within international law, legal protection for refugees, aspects, the scope of protection, and identify the incompetence. As asylum is one of the most discussed topics as it is considered a burden on the international community, effects it has on the hosted countries, economic, social, and security aspects, studying and analyzing the legal provisions related to refugees in international conventions, especially the Four Geneva conventions and the first and second Additional Protocols since these are the first to organize the principles that limit violations against civilians and refugees.What we have concluded is that international efforts have been established in the field of refugee protection by stipulating their basic rights, which is the right of the individuals to obtain refuge and protection. However, the international community is unable to find realistic and practical solutions to ease of suffering of the refugees, as the obligations and rights imposed are considered satisfactory.
Keywords: refugee protection; legal protection; methods for refugee protection; international conventions; asylum countries